(untitled) (Third Sector Social Economic Review, 2013)
Managements are in need of natural resources to meet consumer needs and to sustain their services. The rise in the demand for natural resources has become a burden on world’s natural resources. As these natural resources are not infinite, and these sources should be used efficiently, the new concept as ""environmental manangment"" came to life and managements have started to implement environmental manangment systems.